White Matter Hyperintensities and Changes in White Matter Integrity in Patients with Alzheimer’s Disease - Wang, Liya (2010)
PURPOSE: White matter hyperintensities (WMHs) are a risk factor for Alzheimer’s disease (AD). This study investigated the relationship between WMHs and white matter changes in AD using diffusion tensor imaging (DTI) and the sensitivity of each DTI index in distinguishing AD with WMHs. SUBJECTS AND METHODS: Forty-four subjects with WMHs were included. Subjects were classified into three groups based on the Scheltens rating scale: 15 AD patients with mild WMHs, 12 AD patients with severe WMHs, and 17 controls with mild WMHs. Fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (D(R)) and axial diffusivity (D(A)) were analyzed using the region of interest and Tract-Based Spatial Statistics methods. Sensitivity and specificity of DTI indices in distinguishing AD groups from the controls were evaluated. RESULTS: AD patients with mild WMHs exhibited differences from control subjects in most DTI indices in the medial temporal and frontal areas; however, differences in DTI indices from AD patients with mild WMHs and AD patients with severe WMHs were found in the parietal and occipital areas. FA and D(R) were more sensitive measurements than MD and D(A) in differentiating AD patients from controls, while MD was a more sensitive measurement in distinguishing AD patients with severe WMHs from those with mild WMHs. CONCLUSIONS: WMHs may contribute to the white matter changes in AD brains, specifically in temporal and frontal areas. Changes in parietal and occipital lobes may be related to the severity of WMHs. D(R) may serve as an imaging marker of myelin deficits associated with AD.